Modelos de comportamento judicial sob a ótica realista: evolução, convergências e o problema das decisões políticas - Paulo Morais Milan de Oliveira (2020)
The study of judicial behavior is the study of the motives behind the decisions of judges, and the study of how to predict and explain them. This field has mutated deeply throughout the 20th century: the historical consensus around a legalistic view of judicial behavior, which argues that judges decide based on the mechanical interaction between norms within a legal order, methodological innovations adopted by american political scientists in the interwar period showed evidence contrary to this assumption. From there onward, a veritable Pandora's box was opened and multiple concurring and often mutually exclusive approaches were proposed to further our understanding of judicial behavior. The three main ones were the attitudinal, historical-institutionalist and strategic approaches. Attitudinalists argued that judges behaved in a manner coherent with their political leanings (or "attitudes") over time whenever they dissented; historical institutionalists pleaded that the notion of "path dependence" was relevant to jurisprudence and capable of better explaining behavior, and rejected the careful scientific exploration of this phenomenon by the attitudinalists; and the strategic approach was divided in two different ones. The first one was based on the notion that judges' behavior is similar to that of a rational actor in an economic sense, and that they would strategize (and thus, not act sincerely as attitudinalists defended) so that they could realize their political objetives in a context of interconnected power struggles between various actors. The second one gave up on the idea of classical rationality and argued that judges must be viewed as individuals with their own psychological quirks, which define their objectives; in this instance, they behave strategically in order to realize such objectives, which need not necessarily be rational or in their own self interest. In the end I explore the work of more contemporary scholars who, armed with conceptions and tools from cognitive psychology, test the limits of judicial cognition. I argue that both the psychological strategic approach and the contemporary cognitive one both converge on a view of judicial behavior as composed primarily of intuitive reasoning, and explore briefly the consequences and evidences of such claim.